Inflorescence Development in Abildgaardieae (Cyperaceae, Cyperoideae) - Reutemann Arnolfo, Andrea Guadalupe (2014)
Inflorescences in Cyperaceae are a source of characters with significant systematic value; however, the structure and primary homologies pose a challenge to their interpretation. The relationships among members of Abildgaardieae are not clear due to the absence of a phylogeny with strong support, comprising a representative number of species. Establishing correct primary homologies of inflorescences within Abildgaardieae might help to clarify the relationships among its members, as well as to find synapomorphies for the most important clades. Variations in the mature inflorescences within Abildgaardieae have been related to their ?shape? and ?structure?, and preliminary phylogenetic studies in species of Bulbostylis have shown that inflorescence structure traits are phylogenetically informative, but this is not true for the mere shape. While similar structures in the adult inflorescences of the members of different clades within Abildgaardieae might be considered homologous, it must be ascertained whether such similar structures share the same developmental process or have different developmental patterns. By studying the development of inflorescences in selected species of Abildgaardieae using SEM, we were able to show that inflorescences with homologous structures share a similar developmental process and, therefore, the adult structure of inflorescences may be relied on for establishing correct primary morphological homologies in this plant group. Most structural variations of inflorescences in Abildgaardieae depend on the degree of development of processes shared by the studied species. While phyllotaxis in the main axis of Cyperus may be modified during inflorescence development after primordial inception, variations in the phyllotactic patterns of leaves on vegetative shoots (=nomophylls) and of leaves on fertile shoots (=bracts or hypsophylls) within Abildgaardieae, might establish deeper differences in inflorescence structure, since they depend on changes in the shape of the apical meristem.